Character Education Values in Short Story Collections on Detik.Com and Their Suitability as Teaching Materials in High School - Adianto, Irham Husna; Agus Nuryatin; Haryadi Haryadi (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study examines the values of character education in short stories on Detik.com and their suitability as teaching materials, motivated by changes in the attitudes of teenagers who do not prioritize manners and tend to behave individually. Using a qualitative descriptive method with a pragmatic approach, this study analyzed 23 short stories. This study aims to (1) Describe the values of character education in short stories on Detik.com, (2) Describe the suitability of short stories on Detik.com as teaching materials seen from the aspect of character education values. Data were collected through observation, reading, and notes, with analysis using literature review techniques. The results show that the short stories contain character education values including religious, national, independent, mutual cooperation, integrity, honest, hard work, creative, tolerant, curiosity. The values of independence were found (15 short stories), integrity (12 short stories), religious (5 short stories), nationalism (2 short stories), mutual cooperation (2 short stories), honest (12 short stories), hard work (19 short stories), creative (17 short stories), tolerant (11 short stories), curiosity (15 short stories). Then, from the aspect of suitability as teaching materials in high school, there are 15 short stories on Detik.Com that are suitable as teaching materials seen from the aspect of character education values and there are 8 short stories on Detik.Com that are not suitable as teaching materials seen from the aspect of character education values. This study has implications for the selection of short story-based teaching materials that contain character education values, and are useful for educators in choosing learning resources and for other researchers as a reference for similar studies.